VD_FINDINFO Pron / 2012 / 204 vom 13. September 2012 - VD Tribunal cantonal (2012)
DÉCISION D'IRRECEVABILITÉ, PRIVATION DE LIBERTÉ À DES FINS D'ASSISTANCE | 17 al. 1 CPC, 398d CPC, 398g CPC, 464 al. 2 CPC